Resilient Food Security through ERM and Prophet Yusuf’s Approach - Zahri, Mohd. ‘Adli; Moklis, Nurul Aqidah; Zahri, Fatin ‘Alia; Lestari, Lestari (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: This research examines the alignment between Prophet Yusuf's historical food security strategies and modern Enterprise Risk Management (ERM) frameworks to inform contemporary food security policies. Study Design/Methodology/Approach: A qualitative analysis of historical texts, including interpretations by scholars such as Al-Qurtubi (2008) and Al-Tabari (2009), was conducted to extract key components of Prophet Yusuf's strategies. These components were then compared with current ERM principles to assess their applicability in today's policy context. Findings: The analysis reveals that methods such as predictive risk assessment, strategic grain storage, sustainable resource management, waste reduction, and contingency planning closely mirror modern ERM practices. Integrating these historical strategies can enhance the resilience and effectiveness of current food security policies. Originality/Value: This study bridges historical analysis and modern risk management, offering a unique perspective on the relevance of ancient practices in addressing contemporary food security challenges. It provides actionable insights for policymakers seeking to incorporate proven strategies into modern frameworks, thereby strengthening national and regional food security resilience.